Coverage of a large-scale sporting event in an era of disparate values: an analysis of the opening ceremony of the 2024 Olympics - Gavra D.P.; Savitskaya A.S.; Namyatova K.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the key content characteristics of media accompaniment related to the general tone and theme of the ceremony's assessments. Methods and structure of the study. The article contains a theoretical overview summarizing the research results of foreign scientists. These studies have revealed different and even contradictory audience responses in different countries. The empirical part of the work is devoted to the analysis of media coverage of the opening ceremony in the Russian information field. Results and conclusions. The analysis revealed four groups of critical comments regarding the sports event in question. Unlike the previous opening ceremonies, the fourth category of negative reviews, which has an axiological and political character, stood out clearly. These assessments are caused by the desire of France, as the organizer of the 2024 Olympic Games, to link the universal ideals of Olympism with a global neoliberal and ideologically biased program. Some of the symbols, images and narratives presented at the Paris opening ceremony come into direct conflict with the principles of the Olympic movement and serve the function of separation rather than unification in public policy.